Bringing a mentalizing framework to understanding mothers with addiction: The groundbreaking work of Nancy E. Suchman. Issue 2 (20th March 2023) - Slade, Arietta
Abstract: Nancy Suchman is remembered as a pioneer whose mentalization‐based intervention—Mothering from the Inside Out (MIO)—transformed the treatment of parents struggling with substance use disorders. Specifically, Suchman's work highlighted the neural mechanisms underlying substance use disorders and identified the promotion of parental mentalizing as a key therapeutic focus in enhancing early parent‐child relationships. Her work transformed parenting support models for this population of parents. Several randomized controlled trials (RCT) show the effectiveness of MIO in promoting parental reflective functioning (PRF) and positive relational outcomes in parents with substance use disorders and their children. Suchman's MIO model has since been extended to parenting in many contexts. She is also remembered as a generous colleague, a gifted researcher and clinician, and an inspiration to generations of researchers and practitioners working with parents who aspire to raise healthy, secure children despite multiple challenges and adversities. This special issue compiles the work of researchers inspired by Suchman as they carry on her legacy in examining aspects of parental mentalization. Collectively, the research presented yields confirmation of MIO core assumptions, offers new insights into roles of positive sentiment and savoring in mentalization processes, and presents evaluations of MIO in multiple contexts and with new adaptations. Resumen: A Nancy Suchman se le recuerda como una pionera cuya intervención basada en la mentalización—Cuidados Maternales de Dentro hacia Afuera (MIO)— transformó el tratamiento de progenitores luchando con trastornos de uso de sustancias. Específicamente, el trabajo de Suchman enfatizó los mecanismos neurales subyacentes en los trastornos de uso de sustancias e identificó el promover la mentalización del progenitor como un enfoque terapéutico clave para mejorar las tempranas relaciones progenitor‐niño. Su trabajo transformó los modelos de apoyo a la crianza para este grupo de progenitores. Varios ensayos controlados al azar muestran la eficacia del MIO en cuanto a promover el funcionamiento con reflexión del progenitor y los resultados de una positiva relación en progenitores con trastornos de uso de sustancias y sus niños. El modelo MIO de Suchman desde su creación ha sido expandido a la crianza en muchos contextos. A ella también se le recuerda como una colega generosa, una investigadora y profesional clínica talentosa y como una inspiración para generaciones de investigadores y practicantes profesionales que trabajan con progenitores que aspiran a criar niños saludables y seguros, a pesar de múltiples retos y circunstancias adversas. Este número especial recopila el trabajo de investigadores inspirados por Suchman a medida que ellos continúan el legado en cuanto a examinar aspectos de la mentalización del progenitor. Colectivamente, la investigación presentada aporta la confirmación de las suposiciones centrales del MIO, ofrece nuevas ideas acerca del papel del sentimiento positivo y el aprecio detenido en los procesos de mentalización, y presenta evaluaciones del MIO en contextos múltiples y con nuevas adaptaciones. Résumé: Nous honorons et nous souvenons de Nancy Suchman en tant que pionnière dont l'intervention basée sur la mentalisation – le Maternage de l'Intérieur, en anglais Mothering from the Inside Out (MIO) – a transformé le traitement de parents aux prises avec la toxicomanie. Plus particulièrement le travail de Suchman a mis en lumière les mécanismes neuronaux sous‐jacents aux troubles lié à l'usage d'une substance et il a aussi identifié la promotion de la mentalisation parentale comme une cible thérapeutique clé pour l'amélioration des relations précoces parent‐enfant. Son travail a transformé les modèles de soutien parental pour cette population de parents. Plusieurs essais contrôlés randomisés montrent l'efficacité du MOI pour la promotion du fonctionnement de réflexion parental et des résultats relationnels positifs pour des parents ayant un trouble lié à l'usage d'une substance et leurs enfants. Le modèle MOI de Suchman a depuis été étendu au parentage dans de nombreux contextes. Nous nous souvenons aussi de Nancy Suchman comme étant une collègue généreuse, une chercheuse et une clinicienne talentueuse et une inspiration pour des générations de chercheurs et professionnels travaillant avec des parents qui aspirent à élever des enfants sécures, en bonne santé, malgré de grands défis et l'adversité à laquelle ils peuvent faire face. Ce numéro spécial compile le travail de chercheurs du monde entier, inspiré par Suchman, alors qu'ils perpétuent son héritage en examinant des aspects de la mentalisation parentale. Collectivement ces recherches compilées ici proposent la confirmation des hypothèses principales du MOI, offrent de nouvelles perspectives quant aux rôles du sentiment positif et du fait de savourer dans les processus de mentalisation et présentent des évaluations du MOI dans des contextes multiples et avec de nouvelles adaptations. Zusammenfassung: Ein Mentalisierungsrahmen für das Verständnis suchtkranker Mütter: Die bahnbrechende Arbeit von Nancy E. Suchman Nancy Suchman gilt als Pionierin, deren auf Mentalisierung basierende Intervention ‐ Mothering from the Inside Out (MIO) ‐ die Behandlung von Eltern, die mit Substanzkonsumstörungen kämpfen, verändert hat. Suchmans Arbeit beleuchtete insbesondere die neuronalen Mechanismen, die Substanzkonsumstörungen zugrunde liegen. Außerdem identifizierte sie die Förderung des elterlichen Mentalisierens als therapeutischen Schwerpunkt zur Verbesserung der frühen Eltern‐Kind‐Beziehung. Ihre Arbeit hat die Modelle zur Unterstützung von suchtkranken Elternpopulationen verändert. Mehrere randomisierte kontrollierte Studien belegen die Wirksamkeit von MIO bei der Förderung von elterlichem „Reflective Functioning" und positiven Beziehungs‐Outcomes bei Eltern mit Substanzkonsumstörungen und ihren Kindern. Suchmans MIO‐Modell wurde seither auf Elternarbeit in vielen Kontexten ausgeweitet. Darüber hinaus bleibt sie als großzügige Kollegin, begabte Forscherin und Klinikerin sowie als Inspiration für Generationen von Forschenden und mit Eltern arbeitenden Praktiker:innen in Erinnerung. Ihr Ziel war es, trotz vielfältiger Herausforderungen und Widrigkeiten gesunde und sichere Kinder aufzuziehen. Diese Sonderausgabe stellt die Arbeiten von Forschenden zusammen, die von Suchman inspiriert wurden und ihr Vermächtnis bei der Untersuchung von Aspekten der elterlichen Mentalisierung weiterführen. Die vorgestellten Forschungsarbeiten bestätigen die Kernannahmen von MIO, bieten neue Einblicke in die Rolle positiver Gefühle sowie des Genießens in Mentalisierungsprozessen und stellen Evaluationen von MIO sowohl in verschiedenen Kontexten als auch mit neuen Anpassungen vor. 抄録: 依存症の母親を理解するためにメンタライジングの枠組みを導入する。 ナンシー・E・サッチマンの先駆的な業績 Nancy Suchmanは、メンタライゼーションに基づく介入‐Mothering from the Inside Out(MIO 心の内側からの母親の子育て)により、物質使用障がいに苦しむ親の治療を一変させた先駆者として記憶されている。特に、Suchmanの研究は、物質使用障がいの根底にある神経メカニズムに注目し、人生早期の親‐子関係を促進する上で、親のメンタライゼーションの強化が治療の焦点となることを明らかにした。彼女の研究は、この集団の親に対する子育て支援モデルを一変させた。多数の無作為化比較試験の結果、MIOは、薬物使用障がいのある親とその子どもにおいて、親の内省機能を促進し、関係性を改善する導くことがわかっている。SuchmanのMIOモデルは、その後、様々な文脈の子育てに拡張されている。彼女はまた、寛大な同僚、才能ある研究者であり臨床家、そして、様々な課題や逆境にもかかわらず健康で安心できる子どもを育てたいと願う親と関わる多世代の研究者や実践者を鼓舞させる人として記憶されている。本特集は、Suchmanの遺志を継ぎ、親のメンタライゼーションの側面について探求している研究者の論文で構成されている。掲載論文は、MIOの中核的な仮定を確認し、メンタライゼーションのプロセスにおけるポジティブな感情や味わいの役割について新しい洞察をもたらし、複数の文脈や新しい適応を伴うMIOの評価を提示している。 摘要: Nancy Suchman作为一位先驱而被人们铭记, 她基于心智化的干预措施——"母爱由内而外" (MIO) ——改变了患有药物使用障碍的父母的治疗方法。具体而言, Suchman的工作突出了药物使用障碍背后的神经机制, 并将促进父母的心智化作为一项关键的治疗重点, 以增强早期亲子关系。她的工作改变了这群父母的育儿支持模式。多项随机对照试验表明, MIO在促进药物使用障碍患者的父母反思功能和积极关系方面颇有效果, 同时也使他们的孩子受益。自此以后, Suchman的MIO模型已扩展应用到许多情况下的育儿。她也被视为一位慷慨的同事、才华横溢的研究员和临床医生, 也是一代又一代研究人员和从业者的灵感来源, 他们与父母合作, 渴望在多重挑战和逆境中养育健康、安全的孩子。本期特刊汇集了世界各地受Suchman启发的研究人员的工作, 他们继承了Suchman在研究父母心智化方面的遗产。总的来说, 所呈现的研究证实了MIO的核心假设, 为积极情绪和品味在心智化过程中的作用提供了新的见解, 并在多个背景下对MIO进行了评估和新的调整。 ملخص: استدعاء إطار التركيز الذهني لفهم الأمهات المصابات بالإدمان: العمل الرائد لنانسي إي. سوشمان تُذكر نانسي سوشمان كرائدة أدى تدخلها القائم على التركيز الذهني من خلال برنامج الأمومة من الداخل إلى الخارج (MIO) ‐ إلى إحداث نقلة في علاج الآباء والأمهات الذين يعانون من اضطرابات تعاطي المخدرات. على وجه التحديد ، سلط عمل سوشمان الضوء على الآليات العصبية الكامنة وراء اضطرابات تعاطي المخدرات وحدد تعزيز التركيز الذهني الوالدي باعتباره محورًا علاجيًا رئيسيًا في تعزيز العلاقات المبكرة بين الوالدين والطفل. غيّر عملها نماذج دعم الأبوة والأمومة لهذه الفئة من الآباء. تظهر العديد من التجارب المعشاة ذات الشواهد فعالية MIO في تعزيز الأداء التأملي الوالدي والنتائج العلائقية الإيجابية عند الآباء والأمهات الذين يعانون من اضطرابات تعاطي المخدرات وأطفالهم. منذ ذلك الحين ، امتد نموذج MIO الخاص بـسوشمان ليشمل الأبوة والأمومة في العديد من السياقات. يُذكر أيضًا أنها زميلة كريمة ، وباحثة وطبيبة موهوبة ، ومصدر إلهام لأجيال من الباحثين والممارسين الذين يعملون مع الآباء الذين يتطلعون إلى تربية أطفال أصحاء وآمنين في ضوء التحديات والمحن المتعددة. يضم هذا العدد الخاص عمل الباحثين حول العالم المستوحى من سوشمان وهم يواصلون إرثها في دراسة جوانب التركيز الذهني الوالدي. بشكل إجمالي ، تقدم الأبحاث في هذا العدد تأكيدًا لافتراضات MIO الأساسية ، كما تعرض رؤى جديدة حول أدوار المشاعر الإيجابية والتذوق في عمليات التركيز الذهني ، وتنشر تقييمات لـبرنامج MIO في سياقات متعددة ومع تعديلات جديدة.